Alignment-based genetic programming for real life applications - Vanneschi, Leonardo (2019)
Vanneschi, L., Castelli, M., Scott, K., & Trujillo, L. (2019). Alignment-based genetic programming for real life applications. Swarm and Evolutionary Computation, 44(February), 840-851. DOI: 10.1016/j.swevo.2018.09.006